A STUDY ON PREVALENCE AND COMPLICATIONS OF ABRUPTION IN HYPERTENSIVE DISORDERS OF PREGNANCY IN RELATION TO MATERNAL AND FETAL OUTCOME IN A TERTIARY CARE MATERNITY HOSPITAL - KANTE NAMRATHA; PRASANNA LAXMI D (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of the study was to study the prevalence and complications of abruption in hypertensive disorders of pregnancy in relation to maternal and fetal outcome in a tertiary care maternity center. Methods: It is hospital based prospective observational study done at Government Maternity hospital for period of 2 years. Three hundred and forty antenatal women with hypertensive disorders of pregnancy with gestational age >28 weeks of age more than 20 years, patients are diagnosed mainly on clinical signs and symptoms/ultrasound are included in the study. Results: The prevalence of abruption (36.1%) was seen in 123 among 340 cases of hypertensives. The highest incidence was found among the maternal age of 26 and 30 years (45%). Maximum incidence of abruption was found among those who were between gestational age of 34 and 36weeks accounted for 50%, hence good fetal outcome in terms of fetal birth weight >1500 g. Among cases of abruption, majority of them were severe pre-eclampsia (48.8%), followed by non-severe pre-eclampsia (28.4%), eclampsia (11.3%), G. hypertension (HTN) (8%), and chronic HTN (3.25%). As most of cases of abruption were Grade 1 abruption, accounting for 53.7%, resulting in good maternal and fetal outcome in terms of reduced mortality due to early diagnosis and initiation of treatment. Maternal complications like anemia were seen in 70%, and PPH in 43.3% of cases, are the most common complications encountered. Shock was noted in 24.4%, of cases, and blood transfusions were required in 78.8% of cases. Eighty-six cases (70%) underwent cesarean section, which reduced the maternal and fetal morbidity and mortality. Fetal outcome in terms of birth weight was in the range of 2000–2500 g in 39% of cases, many babies required NICU admissions 72 out of 123, followed by jaundice 93 out of 123, followed by sepsis. Perinatal mortality was 7.7% due to the IUD, 21 seen due to abruption, and 5 due to non-abruption cases. Conclusion: Uncorrected anemia in pregnancy is accompanying cofactor in abruption, leading to an increased need for blood transfusion, morbidity, and mortality of mother. Hence, the need for correction of anemia by diet, iron, and folic acid supplementation, availability of injectable iron at the rural level improves the outcome.